Literasi Dasar Bagi Para Siswa Sekolah Dasar - Bala, Alexander; Genua, Veronika; Larasati, Maria Marietta Bali; Demon, Yosef (Prima Abdika: Jurnal Pengabdian Masyarakat, 2024)
Basic literacy is a basic priority or priority scale that needs to be strengthened and stabilized. The cultivation and formation of basic literacy skills is a real manifestation of the mental revolution program, even mental evolution. Therefore, basic literacy needs to be strengthened because it is the foundation for the lives of future generations. Apart from that, the basic literacy movement that is being intensified aims to support the realization of free humans. What is meant by free humans are free humans who can read and write to gain knowledge and use this knowledge for the good and sustainability of their lives. This article discusses the implementation of Community Service in Rangalaka Village, Kotabaru District, Ende Regency, which will take place from 1 to 30 August 2022. The focus of service activities is the implementation of basic literacy activities in the form of tutoring for students in Rangalaka Village, namely Lewoketo Inpres Elementary School and Satap Ligalejo Middle School. Tutoring is focused on elementary and junior high school students to provide knowledge strengthening, instilling a virtuous attitude in students so that they have good knowledge and attitudes in facing their future.